Pengaruh Penerapan Keselamatan dan Kesehatan Kerja/K3 Terhadap Komitmen Karyawan di PO Bus Juragan 99 Trans Yang Dimediasi Oleh Kepuasan Kerja - Nisa’, Ulfa Khoirun; Pardiman, Pardiman; Amin, Muhammad Sirojuddin (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to analyze the effect of occupational safety and health (OHS) implementation on employee commitment at PO Bus Juragan 99 Trans. Optimal K3 implementation not only serves as an effort to mitigate occupational safety risks, but also as a factor that can increase job satisfaction and employee commitment to the organization. This research was conducted on the bus crew (drivers and co-drivers) of PO Juragan 99 Trans as respondents. The population in this study were all AKAP and Tourism bus crews of PO J99 Trans with a total of 101 people. To determine the number of samples, the Slovin formula was used so that a sample size of 81 people was obtained. The research method used is a quantitative approach with data collection techniques using a questionnaire distributed to the PO Juragan 99 Trans bus crew as respondents. The data analysis method in this study uses Structural Equation Model (SEM) analysis with the help of SmartPLS software to analyze direct effects and indirect effects (mediation). The results showed that the application of OHS has a positive and significant effect on employee job satisfaction. In addition, job satisfaction is proven to act as a mediating variable that strengthens the influence between OHS implementation on employee commitment. With a good OHS policy in place, employees feel safer, more comfortable, and valued, which in turn will increase their commitment such as through increased loyalty and productivity. The implication of this study confirms that companies need to continue to develop comprehensive OHS policies to create a safer and more conducive work environment. Thus, the level of employee satisfaction and commitment can further increase, and contribute to the company's operational efficiency. Keywords: Occupational Safety and Health, Job Satisfaction, Employee Commitment, PO Bus Juragan 99 Trans.